A frameshift mutation of TMPRSS3 in a Chinese family with non-syndromic hearing loss - Jingwen Liang; Zhuoheng Yu; Zhangxing Wang; Jianxia Chen; Yihuan Liu; Zhaoqing Yin; Ruihuan Xu (Frontiers Media S.A., 2022)
BackgroundDeafness is the most common sensory defect in humans worldwide. Approximately 50% of cases are attributed to genetic factors, and about 70% are non-syndromic hearing loss (NSHL).ObjectivesTo identify clinically relevant gene variants associated with NSHL in a Chinese family using trio-based whole-exome sequencing (WES).Materials and methodsWES was performed on the 18-month-old female proband, and her parents. Gene variants specific to the family were identified by bioinformatics analysis and evaluated for their relevance to NSHL. We verified the novel variant in this family by the next-generation sequencing.In order to elucidate the frameshift mutation of TMPRSS3 in a Chinese family, we used the Mass spectrometry to detect the gene from 1,010 healthy subjects.ResultsWe identified a novel homozygous deletion (c.51delA) in exon 2 of the type II transmembrane serine protease 3 gene TMPRSS3, which resulted in a frameshift mutation just before the protein transmembrane domain (p.Q17fs). The deletion was present in the proband and her father, but not in her mother and the healthy controls. We also found mutations with potential relevance to hearing loss in DCAF17, which encodes a protein of unknown function (c. T555A: p.H185Q), and ZNF276, which encodes zinc finger protein 276 (c.1350-2A > G).Conclusions and significanceWe shown a novel frameshift mutation in TMPRSS3 associated with autosomal recessive NSHL in a Han Chinese family.